Peripheral Endogenous Cannabinoid Levels Are Increased in Schizophrenia Patients Evaluated in a Psychiatric Emergency Setting - Potvin, Stéphane; Mahrouche, Louiza; Assaf, Roxane; Chicoine, Marjolaine; Giguère, Charles-Édouard; Furtos, Alexandra; Godbout, Roger (Frontiers in Psychiatry, 2020)
Background: The endogenous cannabinoid system, which mediates the psychoactive effects of cannabis in the brain, may play a key role in the pathophysiology of schizophrenia. While some studies have shown that the levels of anandamide, an endogenous cannabinoid ligand, are increased in the cerebrospinal fluid of schizophrenia patients, studies measuring anandamide levels in the periphery have produced inconsistent results. Here, we sought to determine if the assessment of endocannabinoids in patients from a psychiatric emergency setting would produce more conclusive results. Methods: One hundred seven patients with a schizophrenia-spectrum disorder from the psychiatric emergency settings of the Institut Universitaire en Santé Mentale de Montréal and 36 healthy volunteers were included in the study. Psychotic symptoms, anxious and depressive symptoms and substance use were assessed using self-report questionnaires. In addition to anandamide, the levels of oleoylethanolamide (OEA), an anorexigenic fatty-acid ethanolamide, were also measured, since the prevalence of the metabolic syndrome is increased in schizophrenia. Plasma levels of anandamide and OEA were measured using liquid chromatography and mass spectrometry. Results: Plasma anandamide and OEA levels were significantly increased in schizophrenia patients, relative to controls (Cohen's d=1.0 and 0.5, respectively). Between-group differences remained significant after controlling for metabolic measures. Importantly, the levels of both endocannabinoids significantly decreased after discharge from the emergency setting. Conclusion: The current results add to the growing body of evidence of endocannabinoid alterations in schizophrenia. The strong elevation of plasma anandamide levels in schizophrenia patients assessed in the psychiatric emergency setting suggests that anandamide and OEA area potential biomarkers of the psychological turmoil associated with this context.